PENGARUH DAYA SAING PERUSAHAAN DAN FREE FLOW OF SKILL LABOUR DALAM ECONOMIC ANALYSIS OF LAW - Iwan Sandi Pangarso (Jurnal Justiciabelen, 2018)
With the ease with which the permission of Foreign Workers (TKA) to enter Indonesia is expected to have a positive influence both for individuals, companies and for the country. The ease of permitting foreign workers can also be a way for investors to invest in Indonesia where investments made will be very profitable for the country. With the ease of Foreign workers permits, it is expected to be a trigger for the people of Indonesia to continue to develop and advance so as not to be left behind by the Foreign Workers and be able to develop companies in Indonesia more advanced so as not to make alternative foreign workers for company development. In relation to the competitiveness of companies, selected foreign workers must be able to develop the company so that they are able to compete in the world economy. Thus Indonesian workers and workers must be able to work together in producing new alternatives that can be developed in Indonesia, with the same welfare so as not to trigger discrimination between the two parties concerned. The government here has a very important role in everything, especially in the welfare of its people, here is done by opening up employment opportunities and guaranteeing all the welfare of its people by paying attention to the existing work by increasing the nominal salary in order to improve welfare for all levels of society especially people who are in the lowest layer.